Niesprawiedliwy Bóg w psalmach? - Węgrzyniak, Wojciech (Verbum Vitae, 2014)
The Book of Psalms describes God as righteous. The aim of this article is to answer the question whether one can speak of the injustice of God in the Psalms. First, the author tries to draw some conclusions from the statistics of words describing God’s righteousness. Then, he summarizes the studies dealing with the topic in question. Next, he analyses the four Psalms that speak more or less directly about the injustice of God (Ps 44 , 69, 88, 89). At the end, the author attempts to answer the question what the genre of the psalms has to do with talking about an unjust God. The final conclusions include the following statements: 1) generally the Psalms do not speak about unjust God; 2) the exceptions are a sign of an extremely dramatic situation of the nation; 3) injustice is seen as a temporal problem and therefore resolvable ; 4) God’s injustice may involve a curse addressed to an enemy; 5) death is the only limitation of the justice of God.